A Historical Overview of English Language Teacher Preparation Programs in Iranian Private Language Institutes - Leila Tajik; Sara Pakand Ahmadi; Seyyed-Abdolhamid Mirhosseini (Journal of Modern Research in English Language Studies)
Given the significant role of studying history in casting light on the past and present of events and providing future insight, the present study aimed to investigate the history of English teacher preparation programs offered in five famous private language institutes established in the second post-revolutionary decade (about thirty years ago) in Iran. Precisely, the study investigated the past and present of the programs in terms of their internal aspects as well as their response to external or sociopolitical associations of English language teaching (ELT) from their establishment. Two administrators, nine TPP (teacher preparation program) designers who were also teacher instructors, and two teachers were purposefully sampled. Data was gathered through conducting semi-structured interviews, in addition to analyzing documents available on the website of the institutes and those provided by the participants. Analyzing data through phronetic iterative approach manifested the related history in terms of five constant features including methodological directions as content, transmission approach in teacher preparation, providing teachers with external opportunities for professional development, insisting on monolingualism in ELT, and disregard for bringing the inclusion of local culture in ELT to the attention of prospective teachers, as well as three major changes comprising inclusion of teaching practice (TP), inclusion of technology education for ELT purposes following the outbreak of covid-19 pandemic, and enhancement of TPP duration. Specifically, the constant features disclosed lack of attention to external association of ELT in designing the programs while the major changes exhibited their internal development. Findings have implications to develop teacher preparation programs based on postmethod pedagogy.